Functional properties and toxicological analysis of nanocellulose-based aerogels loaded with polyphenols from Hyeronima macrocarpa berries - Andrés Felipe Alzate-Arbeláez; Farid B. Cortés; Benjamín A. Rojano (Food Hydrocolloids for Health)
In this study, the nutraceutical properties of ethanolic extract of Hyeronima macrocarpa fruits, immobilized on nanocellulose-based aerogels (NCAG) synthesized from the seeds were studied. Specifically, bioactives with antioxidant properties of the pulp were determined, NCAG and homologs of acetate (NCAG-A) and sulfate (NCAG-S) were obtained, and characterized from the seed, the aerogels loaded with antioxidants were studied to determine the anti-radical activity, digestion patterns, protein oxidation inhibition, and toxicological properties. The berries presented a high anthocyanin content of 1317.4 mg C3G/100 g FW and ORAC value ​​of 12,732 µmol Trolox/100 g FW, which make an important source of antioxidants. The seeds presented cellulose content of 61.4 % with a NC yield of 38.4 %. NCAG and their surface homologs were successfully synthesized and characterized by FTIR, DLS, and TEM finding the characteristic bands of the main functional groups, NC presented particle sizes ranging from 64 to 141 nm, BET analysis showed surface areas of 71.1, 102.3, and 183.5 m2/g for NCAG-A, NCAG, and NCAG-S, respectively, and pore sizes of 36–38 nm called mesopores. NCAG presented the highest capacity to trap reactive oxygen species (106.8 mg catechin Eq./g., 86.5 % OH• trapped, respectively). All samples showed the capacity to delay the oxidation of a protein system in a dose-dependent manner, with IC50 values ​​of 70 mg/L (NCAG), 176.3 mg/L (NCAG-A), and 255.6 mg/L (NCAG-S). In vitro digestion showed that NCAG-S was more efficient in delivering anthocyanins under gastric conditions (bioaccessibility of 59.3 %), and NCAG under duodenal conditions (bioaccessibility of 88.2 %). The differences found in samples for the different functional assays can be explained by the various types of interactions generated between the antioxidant molecules and aerogels, in the various media where the analyses are carried out. The results indicate nanocellulose-based aerogels, synthesized from lignocellulosic residues of H. macrocarpa seeds, proved to be porous matrices capable of carrying bioactive substances, and presented interesting properties for the delivery and conservation of antioxidant molecules such as anthocyanins and other polyphenols, achieving an in vitro protective effect against the oxidation of biomolecules.